2017
DOI: 10.1136/bmjopen-2017-018307
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the role of modifiable risk factors in the differences in cardiovascular disease mortality rates between metropolitan and rural populations in Australia: a macrosimulation modelling study

Abstract: ObjectivesThe study aimed (1) to quantify differences in modifiable risk factors between urban and rural populations, and (2) to determine the number of rural cardiovascular disease (CVD) and ischaemic heart disease (IHD) deaths that could be averted or delayed if risk factor levels in rural areas were equivalent to metropolitan areas.SettingNational population estimates, risk factor prevalence, CVD and IHD deaths data were analysed by rurality using a macrosimulation Preventable Risk Integrated Model for chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 20 publications
2
45
0
3
Order By: Relevance
“…Those living outside of major cities also have higher proportions of CVD risk factors, such as obesity, smoking, high‐risk alcohol use and inadequate physical activity, 2,37 with a national study finding that 38.2% of the gap in IHD death rates between urban and rural populations could be attributed to differences in modifiable risk factors 49 . However, it is difficult to attribute these differential risk factor profiles to remoteness alone, as many of the same factors are associated with socioeconomic disadvantage 10…”
Section: Discussionmentioning
confidence: 99%
“…Those living outside of major cities also have higher proportions of CVD risk factors, such as obesity, smoking, high‐risk alcohol use and inadequate physical activity, 2,37 with a national study finding that 38.2% of the gap in IHD death rates between urban and rural populations could be attributed to differences in modifiable risk factors 49 . However, it is difficult to attribute these differential risk factor profiles to remoteness alone, as many of the same factors are associated with socioeconomic disadvantage 10…”
Section: Discussionmentioning
confidence: 99%
“…There is a known higher prevalence of risk factors, such as rates of alcohol consumption and obesity in rural Australia [24]. Alston and colleagues have reported that one-third of the excess CVD deaths in rural residents were due to risk factors, and that approximately 1461 deaths from CVD could be delayed annually, reducing the rural-urban mortality gap by 38.2% if rural Australian residents had the same levels of risk factors as those in metropolitan areas [25].…”
Section: Preventionmentioning
confidence: 99%
“…Globally, these rural inequalities have been associated with poorer access to health care, geographical isolation, lower incomes, reduced access to healthy foods, and differences in modifiable behavioural risk factors such as smoking 3-6 . A recent Australian study found that if rural Australians could achieve the same levels of dietary intake, smoking cessation, alcohol intake and physical activity as their metropolitan counterparts, the rural–metropolitan disparity in ischaemic heart disease mortality would decrease by 38% 7 . About 7 million Australians live in rural, regional and remote areas, as defined by the Australian Statistical Geography Standard (ASGS), with evidence of poor diet and increased disease burden 8,9…”
Section: Chapter 1 Retail Initiatives To Improve the Healthiness Of Fmentioning
confidence: 99%